Occupational safety and health management system (OSHMS) guideline compliance among medical laboratories in Klang Valley - I Anuar,; F Zahedi,; A Kadir,; A.B Mokhtar, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Background : Nowadays, most medical laboratories in Malaysia practice occupational safety and health based on standard operating procedure and sometimes ad-hoc characteristic limited to only internal use. The level of compliance of the national occupational safety and health management system (OSHMS) guidelines among medical laboratories in Malaysia is still largely unexplored. Methods : This study was carried out on 34 medical laboratories consisting of 17 public medical laboratories and 17 private medical laboratories in Klang Valley using self-administered questionnaire based on guideline of OSHMS6. This study covered 112 medical laboratories units including pathology chemistry (18), microbiology (20), virology (7), histopathology (16), cytopathology (17), hematology (19) and 15 multi discipline medical laboratories. Results : This study showed the level of compliance to the national OSHMS guideline among medical laboratories who are MS ISO 15189:2004 accredited & have a higher scores (p<0.01) in mostly measurement indicators and measurement indicators, such as element of polices (7.2% vs. 53.5%), organizing (71.5% vs. 54.9%), evaluation (77.1% vs. 52.8%) and action for improvement (86.2% vs. 50.6%) compared to those do not have that accreditation except in the of planning and implementation (86.2% vs. 50.6%) which is not significant statistically. However, there are significant difference (p<0.05) between government medical laboratories and private medical laboratories. There are no significant difference (p>0.50) between medical laboratories which have ISO 9000 quality management system certification or not compared to level of compliance to the national OSHMS guideline among medical laboratories and the laboratories operating more than 10 years compared to those with less than 10 years of operation as well towards implementing to OSHMS. Conclusion : This study showed that medical laboratory which is accredited with MS ISO 15189 is more compatible in terms of compliance to the national OSHMS guideline compared to other management system.